Pop-Up Book–Based Psychoeducation Improves Self-Esteem and Strengthens Bullying Prevention Among Elementary School Children - Dian Putri Eriyanti; Endang Caturini Sulistyowati; Dwi Ariani Sulistyowati (JKG (JURNAL KEPERAWATAN GLOBAL), 2026)
Background: Bullying is a serious problem that is repeatedly. Bullying can be experienced by a person because they have low self-esteem. One way to overcome bullying is to increase children’s self-esteem from an early age through bullying prevention psychoeducation   with pop-up book media. This study aims to determine the effect of psychoeducation on bullying prevention with pop-up book media on self-esteem in 3 Kacangan public elementary school children. Methods: This type of quantitative research uses a pre-experimental design with a one-group pretest-posttest design. The sampling technique used was purposive sampling with 36 respondents. The instrument used is the Rosenberg Self-Esteem Scale (RSES). The intervention was carried out 3 times, and data analysis was performed using Paired T-Test. Results: The results of the analysis of the paired sample t-test self-esteem from 36 respondents showed an increase in the level of self-esteem with a p value of < 0.001, so that there was a psychoeducational effect on bullying prevention with pop-up book media on self-esteem in elementary school children. Conclusion: There is an effect of psychoeducation on bullying prevention with pop-up book media on self-esteem in elementary school children. The use of interactive and interesting educational media can increase students' understanding of the causes, impacts, and ways to prevent bullying so that students are better able to control their social behavior. In addition, increasing self-esteem in students is an important factor in forming confidence, positive attitudes, and children's ability to interact healthily with peers.